2020
DOI: 10.3201/eid2601.191165
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Infections in Dromedary Camels, Nigeria and Ethiopia, 2015–2017

Abstract: We examined nasal swabs and serum samples acquired from dromedary camels in Nigeria and Ethiopia during 2015–2017 for evidence of influenza virus infection. We detected antibodies against influenza A(H1N1) and A(H3N2) viruses and isolated an influenza A(H1N1)pdm09–like virus from a camel in Nigeria. Influenza surveillance in dromedary camels is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…Another study showed positive serological results for both H1N1 and H3N2 viruses in the sera of camels from Nigeria [24]. The results of this study have limitations since some species were not represented by an adequate number of samples.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Another study showed positive serological results for both H1N1 and H3N2 viruses in the sera of camels from Nigeria [24]. The results of this study have limitations since some species were not represented by an adequate number of samples.…”
Section: Resultsmentioning
confidence: 71%
“…In KSA, molecular surveillance of influenza type A virus showed that only 1.7% of the imported camels from Africa were positive [ 22 ]. Another study showed positive serological results for both H1N1 and H3N2 viruses in the sera of camels from Nigeria [ 24 ]. The results of this study have limitations since some species were not represented by an adequate number of samples.…”
Section: Resultsmentioning
confidence: 99%
“…dogs (Dundon et al, 2010), elephants (Paungpin et al, 2017), dromedary camels (Chu et al, 2020), wild tigers (Panthera tigris) (Sangkachai et al, 2019), giant panda (Ailuropoda melanoleuca) (Li, Zhu, et al, 2014), northern sea otters (Enhydra lutris kenyoni) (Li, Ip, et al, 2014) and northern elephant seals (Mirounga angustirostris) (Goldstein et al, 2013). These domestic and wild animals were considered naturally infected with A(H1N1)pdm09 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown, for the first time, humoral immune responses in cheetahs induced by natural infection of influenza A virus. Antibodies specific to A(H1N1)pdm09 viruses have been detected in a variety of animals, including domestic cats (Ali et al., 2011), dogs (Dundon et al., 2010), elephants (Paungpin et al., 2017), dromedary camels (Chu et al., 2020), wild tigers ( Panthera tigris ) (Sangkachai et al., 2019), giant panda ( Ailuropoda melanoleuca ) (Li, Zhu, et al., 2014), northern sea otters ( Enhydra lutris kenyoni ) (Li, Ip, et al., 2014) and northern elephant seals ( Mirounga angustirostris ) (Goldstein et al., 2013). These domestic and wild animals were considered naturally infected with A(H1N1)pdm09 viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation